The Effect of Tax Planning, Deferred Tax Burden, and Profitability on Earnings Management in Industrial Companies - Michaela Igari Talita; Muhammad Malik Muhammad; Brigitta Dominic Tander (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Earnings management is a company's practice of manipulating financial indicators or accounting data for specific purposes. The aim of this study is to determine the effect of tax planning, deferred tax burden, and profitability on earnings management. This study uses a purposive sampling method and Statistical Package for the Social Sciences Version 27 (SPSS) software for data processing. The sample used in this study were industrial companies listed on the Indonesia Stock Exchange for the period 2019–2022. The results of this study indicate that tax planning affects earnings management, while deferred tax charges and profitability do not.